2011
DOI: 10.1007/s00192-011-1454-8
|View full text |Cite
|
Sign up to set email alerts
|

Hands on or hands off the perineum: a survey of care of the perineum in labour (HOOPS)

Abstract: The "hands off" the perineum technique is prevalent in the management of labour. We hypothesise that a possible consequence might be an increased incidence of obstetric anal sphincter injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 29 publications
0
50
0
3
Order By: Relevance
“…Changes in the application of perineal protection techniques may also have played a role. [68][69][70][71] The implementation of manual assistance and perineal protection techniques during the second stage of labour have significantly reduced the incidence of perineal tears in Norway. 72,73 Antenatal perineal massage reduces the likelihood of perineal trauma (mainly episiotomies), but is not routinely practiced in the UK.…”
Section: Comparison With Previous Literaturementioning
confidence: 99%
“…Changes in the application of perineal protection techniques may also have played a role. [68][69][70][71] The implementation of manual assistance and perineal protection techniques during the second stage of labour have significantly reduced the incidence of perineal tears in Norway. 72,73 Antenatal perineal massage reduces the likelihood of perineal trauma (mainly episiotomies), but is not routinely practiced in the UK.…”
Section: Comparison With Previous Literaturementioning
confidence: 99%
“…5 In this time period, while the obstetric community debated whether delivery of the child should be by hands-on or hands-off, a shift was noted from hands-on to hands-off among midwives in the UK6 as well as in Scandinavian countries 78 Recent observational studies from Norway, however, showed a reduction of OASIS from around 6 % to 3 % in vaginally delivering first time mothers when implementing a hands-on technique 9…”
Section: Introductionmentioning
confidence: 99%
“…The results of the present study are supported by the results of Wu et al on 77 midwives in Singapore, in which maternal factors, neonatal factors and midwives factors were associated with increased risk of episiotomy. 13,14 Some delivery practices, such as 'hand on' compared with 'hands poised' for perineal guarding have been shown to be associated with higher rates of episiotomy, 15 and provider experience, beliefs and training are other potential factors that may influence episiotomy rates. 16 Improving midwifery care during delivery (giving enough time to the mother, encourage mother to be cooperate, no supine position and premium support during delivery, increase movement of the mother), reforming health system and health policy (increase number of midwives, decrease number of mothers admitted, no early admission, no giving early piton, supporting midwives, encourage for home delivery) and improving maternal care during pregnancy ( prenatal education and exercise, normal baby size) were midwives' opinion for decreasing the rate of episiotomy.…”
Section: Resultsmentioning
confidence: 99%